Removal of Dissolved Organic Carbon from Peat Swamp Runoff Using Assorted Tropical Agriculture Biomass - Sim, F. S.; Mohd Irwan Lu, N. A. L.; Lee, Z. E. T.; Mohamed, M. (Universiti Putra Malaysia Press, 2015)
In this study, agriculture biomass was used to remove dissolved organic matter from peat swamp runoff. The functional groups and morphological properties of 6 tropical agriculture biomasses (coconut husk, rice husk, empty fruit bunch, sago hampas, saw dust and banana trunk) in their raw and citric acid–treated states were examined. The Fourier transform infrared (FTIR) spectra showed that various biomasses were typically characterised with lignocellulosic compounds. The spectra analysis further demonstrated that citric acid treatment resulted in the dissolution of lignin and hemicelluloses to various extents where carboxyl groups were also introduced. These changes hypothetically suggest improved adsorption ability. Treatment of peat swamp runoff with various untreated biomasses showed no adsorption. With the modified biomass, adsorption was evidenced, with rice husk illustrating the highest removal efficiency of 60% to 65%.The biosorbent can be used in the water treatment process especially for treating water with a high dissolved organic matter content. The spent sorbent can be subsequently applied as a soil conditioner as the dissolved organic fraction, commonly known as humic matter, possesses important agricultural value.